Analysis of Pre-service History Teachers’ Attitudes Toward the Use of Distance Education Environments - Alaca, Eray; Agbal, Sema (Angstrom Centre of Education, 2025)
The purpose of this study is to analyze attitudes of pre-service history teachers toward the use of distance education environments. It was examined whether attitudes of pre-service history teachers toward using distance education environments differed by gender, class, internet access, and device type. The research study group consisted of 86 pre-service history teachers studying in the History Department of the Faculty of Science and Literature at a Turkish state university. As data collection tools, the